2002
DOI: 10.1034/j.1399-3038.2002.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic conditions in 5–8‐year‐old Maltese schoolchildren: Prevalence, severity, and associated risk factors [ISAAC]

Abstract: Allergic conditions, especially asthma, seem to be increasingly common worldwide. The International Study of Asthma and Allergies in Childhood (ISAAC) was the first study carried out worldwide using standardized questionnaires in order to create a reliable global map of childhood allergy. The Maltese Islands were one of the centres that participated in this study and in this article the data obtained from 3,506 5-8-year-old children from 24 state schools (78.5% response rate), and also data obtained from some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
2
18
2
1
Order By: Relevance
“…We only found that family smoking either currently or at child's birth has weak associations with child's wheeze ever or in the last 12 months (Table 4). We also found no significant associations between parental smoking (both paternal and maternal smoking) and child's rhinitis and hay fever, which are consistent with previous studies [3,24,25]. Therefore, smoking among parents may be not a strong risk factor for respiratory symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We only found that family smoking either currently or at child's birth has weak associations with child's wheeze ever or in the last 12 months (Table 4). We also found no significant associations between parental smoking (both paternal and maternal smoking) and child's rhinitis and hay fever, which are consistent with previous studies [3,24,25]. Therefore, smoking among parents may be not a strong risk factor for respiratory symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…A review also found that effective tobacco smoke control can rapidly reduce the prevalence of respiratory diseases [21]. However, several studies found no association between parental smoking and asthma [22,23], wheeze [23,24], hay fever [24,25] or rhinitis [3,25]. Moreover, a study conducted by ISAAC Phase One Study Group, found that "countries that have high adult male smoking rates have a lower risk of asthma and rhinitis symptoms in children" [26].…”
mentioning
confidence: 99%
“…The prevalence of allergic conditions in Maltese schoolchildren was already of major concern in 1994/95 following the results of ISAAC phase 1 in the Maltese Islands. These revealed that our schoolchildren in the younger age group, both 5‐ to 8‐yr‐olds (1) and 13‐to 15‐yr‐olds (2), were very commonly and severely affected by wheezing, rhinitis and eczema even when compared to other nations taking part in this worldwide study (3). Another worrying finding was that, in the case of the 5‐to 8‐yr‐old age group, asthma and rhinitis continued to rise steadily in prevalence over the 7 ensuing years between phase 1 and phase 3 of the ISAAC study in the Maltese Islands (4).…”
mentioning
confidence: 78%
“…Informed consent was obtained from the participants before starting the interview by phone. For the development of the study questionnaire, the International Study of Asthma and Allergies in Childhood instrument [19] was used. The investigators supplemented it with additional questions related to the topic of interest.…”
mentioning
confidence: 99%